Connection Class Mother Pregnant With Readiness Mother Facing Childbirth in the Work Area of Gela Health Center, North Taliabu District Masriyani - Masriani (Journal of Health Science Community, 2025)
Pregnant women's classes are one form of activity carried out by health workers to improve mothers' knowledge and understanding of pregnancy and childbirth preparation. Pregnant women's class activities in the Gela Health Center Work Area, North Taliabu District are still very low due to several factors, namely the low level of maternal education, support from husbands or families which is lacking and also because of the family economy or a small family income that causes mothers to be less prepared to face childbirth. This type of research uses an analytical survey with a cross-sectional study approach, the population in this study was 79 pregnant women, with a sampling technique using Simple Random Sampling , 66 respondents were obtained. Data collection was carried out by direct interviews using questionnaires. By using the Chi-Square statistical test to determine the relationship between the two Independent and Dependent variables. The results of the study from 66 Respondents obtained Most of the respondents who participated were quite follow class Mother pregnant And Ready For face labor as much as 23 Respondents (34.8%) while respondents who did not participate and were not ready to face childbirth were as many as (65.2%).Results analysis use test statistics Chi-Square obtained results P=0.00 < 0.05, so Hey in reject And Ha accepted Which means There is connection between Class Mother pregnant with readiness Mother face labor in Region Work Health Center Gela Subdistrict Taliabu North. It is expected to always be active in attending pregnancy classes because in this pregnancy class mothers can learn about pregnancy, signs and dangers of pregnancy and how the labor process is good so that mothers are ready to face labor without any doubt.